PENGARUH PERAN INFLUENCER DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN PRODUK GLAD2GLOW DI SURAKARTA - Eza Agfonicha Vefiadytria; Mirzam Arqy Ahmadi (Cahaya Ilmu Bangsa, 2024)
Information and communication technology developments enable consumers to connect better with brands through social media. The Research aims To Analyze How Influencers Influence Purchasing Decisions. This Research Method uses Theoretical Studies Literature Theory and a Literature Review Approach, While Data Analysis Uses Descriptive Methods that describe Findings from The Literature. Research Results Influencers Act as Opinion Leaders on Social Media Who Provide Recommendations for Their Followers to Trust in Various Product Categories. These Influencers are very much Sought After by Various Business People to Market their Products by Creating Content in the Form of Videos and Images Using These Influencers to Attract the Interest of Their Followers.